Electron Holography: Advanced Electron Holography Applied to Electromagnetic Field Study in Materials Science (Adv. Mater. 25/2017). Issue 25 (3rd July 2017) - Shindo, Daisuke; Tanigaki, Toshiaki; Park, Hyun Soon
Abstract : Advances and applications of electron holography toward the study of electromagnetic fields in various functional materials are presented by Daisuke Shindo and co‐workers in article number1602216 .